Diversity and genetic structure of the monotypic genus colombobalanus (fagaceae) in southeast of colombian andeans (2013)
Colombobalanus is a genus with a single species Colombobalanus excelsa, currentlycategorized as vulnerable (VU) and known from only five localities in the ColombianAndes. We analyzed the diversity and genetic structure of four C. excelsa forestremnants in one locality in the coffee-producing area of the southeastern corner ofDepartment of Huila, Colombia. Samples from ten trees were collected from each forestremnant for a total of 40 sample leaves, which were analyzed using 7 microsatellitemarkers. The resulting data matrix was used to perform genetic diversity (He), geneticstructure (FST), and genetic distance analyses, as well as the Jaccard similarity index.Fourteen alleles were found for the entire population, with a heterozygosity (He) of0.2797 and a genetic structure (FST) of 0.049. These indices suggest that the forestremnants are members of a panmictic population with historical patterns of geneticflow. The results also allow us to conclude that the low number of alleles found inthese populations compared with other populations in the country show a signature ofhistorical bottleneck in these forest remnants, where few individuals were seedlingsof C. excelsa due to the disturbances caused by human activity